2019
DOI: 10.2196/13713
|View full text |Cite
|
Sign up to set email alerts
|

“Call a Teenager… That’s What I Do!” - Grandchildren Help Older Adults Use New Technologies: Qualitative Study

Abstract: Background Although family technical support seems intuitive, there is very little research exploring this topic. Objective The objective of this study was to conduct a subanalysis of data collected from a large-scale qualitative project regarding older adults’ experiences in using health information technology. Specifically, the subanalysis explored older adults’ experiences with technology support from family members to inform strategies for promoting older adults’ en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…The review identified 16 studies including seven RCTs that studied self‐management support, quality of life, and health service utilization (Table 1). 70–86 These health IT interventions were delivered via patient portal, remote patient monitoring technology, patient‐reported outcome collection applications, and telemedicine virtual coaching 72,73,78,79,81,82,87 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review identified 16 studies including seven RCTs that studied self‐management support, quality of life, and health service utilization (Table 1). 70–86 These health IT interventions were delivered via patient portal, remote patient monitoring technology, patient‐reported outcome collection applications, and telemedicine virtual coaching 72,73,78,79,81,82,87 …”
Section: Resultsmentioning
confidence: 99%
“…These barriers inhibit interactive feedback from clinicians and lower patient motivation to stay engaged in self‐management 82,83 . Also, PLWMCC are often older adults who rely on family/caregivers for technical support, but family members reported that they lacked confidence to give this training, struggled to explain simple technology tasks, and were frustrated by the slow learning process 80 . These two qualitative studies assessed the usability and acceptance of telemonitoring with regard to MCC self‐management 83,85 .…”
Section: Resultsmentioning
confidence: 99%
“…Taking end users into account increases the usability, uptake, and effectiveness of interventions [ 92 ]. After developing a new mobile app, it is essential to invest time in training tools, in-person training, user manuals, and support hotlines regarding the use of mobile app, as many older adults want to receive technical and social support for the installation, exploration, and learning of a mobile app [ 16 , 74 , 93 - 95 ]. Only making mobile apps available in the app stores will fail to optimize their use by older adults [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Promotion measures as reimbursement of costs of mobile apps with proven effectiveness through health care providers and targeted information campaigns on existing high-quality mobile apps for older adults and their relatives could help them to integrate high-quality mobile apps into their daily lives [ 93 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low health literacy similarly benefit from the involvement of trusted family or friends during medical visits [ 17 , 18 ]. Prior studies among older patients have confirmed that family members facilitate patient access and use of the patient portal [ 19 , 20 ] and utilize the patient portal for the patient [ 21 - 25 ]. Given that these patients are interested in sharing electronic health information with family members or close friends [ 19 , 20 , 26 , 27 ], tailored strategies are needed to engage family members or friends in accessing health care digitally, especially in safety-net settings with a majority proportion of vulnerable patients and where caregivers play a key role in patient care.…”
Section: Introductionmentioning
confidence: 99%